Identifikasi Terumbu Karang di Zona Perairan Neritik Pulau Nangka Besar, Bangka Tengah - Yunita Lestari (Biology Study Program, Faculty of Science and Engineering, University of Bangka Belitung, Indonesia, 2025)
Nangka Island have shallow areas that fit the criteria of coral life. The purpose of this practicum is to identify the type and find the locations where the corals grow in the waters of the neritic zone of Nangka Besar Island. Practicum method by sampling in the form of coral reefs that are still alive in the waters of the neritik zone of Nangka Island. The coral reefs taken are coral reefs that can be covered by divers. Coral reefs below sea level (depth 2-3 meters) are lifted up on the ship by hand. In addition, visual observations and documentation and free collection are carried out using the help of snorkels. Types of coral reefs found and identified in the waters of Nangka Besar Island there are 2 types of coral reefs and are derived from the genus Porites. The types found are Porites lobata and Porites napopora. The location of the coral reef is located 100-200 meters from the mainland, where the growth of coral reefs is around large rocks with an estimated depth of 1.5 meters from sea level. Based on observations, coral reefs are marine bioata habitats such as sea urchins, shrimps,crabs, snake stars, and sea worms.